एसपीए में यूनिवर्सल डिजाईन कार्यशाला - (:unkn) unknown (नईदुनिया, 2012)
SPA, Bhopal were organizing ‘Universal Design Workshop’ from 06th to 8th October 2012, in collaboration with UNESCO Development and Research Organization for Nature, Arts and Heritage Foundation, New Delhi, Archaeological Survey of India, Ministry of Culture, Govt. of India and National Association for Student of Architecture at MANIT campus.
Keywords: SPA Bhopal Workshop; Universal Design Workshop; National Student Design Competition 2012